SCHWANN CELLS: LEADER OF NERVENKITT - Mirajullah, Muhammad; Xinya, Shen (Journal of Ayub Medical College Abbottabad, 2002)
Schwann cells (SC) are the major & only glial cell element of peripheral nervous system (PNS) which by virtue of their unique biological activities give the distinction of regeneration not only to the peripheral nervous system (PNS) but also induce regeneration in the central nervous system (CNS) by changing the hostile & inhospitable environments around its neurons to neurite promoting favourable conditions. These multifunctional cells synthesize, secrete & express many neurotrophic, neurotropic, neurite promoting & growth factors, major myelin glycoproteins, cell adhesive molecules (CAMs), basement membrane components as well as a cornucopia of receptors at various stages of life. Their important role in neural tissue development, organization & maintenance cannot overshadow their emerging vital contributions to the ongoing studies on demyelinating diseases (e.g. multiple sclerosis) & other debilitating and disfiguring neurological defects (e.g. neurofibromatosis). Underlying SC defects may be responsible for abnormalities in peripheral neuropathies. SC are the primary cells in the disfiguring disease of neurofibromatosis as well as shoulder the responsibility for Schwannoma & Neurilemoma tumours. Their versatility is evidenced by their phagocytic nature during Wallerian & traumatic degeneration. They are indispensable to the normal functioning of axons. Inhibiting their proliferation at the stage of regeneration not only retards axonal growth but profoundly impairs myelination. Their proliferation & physical presence is a prerequisite for the reparative process providing a proper terrain or scaffolding essential for the regeneration & survival of neurons.